Mitogen-Inducible Gene 6 Inhibits Angiogenesis by Binding to SHC1 and Suppressing Its Phosphorylation - Liu, Lixian; Xing, Liying; Chen, Rongyuan; Zhang, Jianing; Huang, Yuye; Huang, Lijuan; Xie, Bingbing; Ren, Xiangrong; Wang, Shasha; Kuang, Haiqing; Lin, Xianchai; Kumar, Anil; et al. (Frontiers in Cell and Developmental Biology, 2021)
The mitogen-inducible gene 6 (MIG6) is an adaptor protein widely expressed in vascular endothelial cells. However, it remains unknown thus far whether it plays a role in angiogenesis. Here, using comprehensive in vitro and in vivo model systems, we unveil a potent anti-angiogenic effect of MIG6 in retinal development and neovascularization and the underlying molecular and cellular mechanisms. Loss of function assays using genetic deletion of Mig6 or siRNA knockdown increased angiogenesis in vivo and in vitro, while MIG6 overexpression suppressed pathological angiogenesis. Moreover, we identified the cellular target of MIG6 by revealing its direct inhibitory effect on vascular endothelial cells (ECs). Mechanistically, we found that the anti-angiogenic effect of MIG6 is fulfilled by binding to SHC1 and inhibiting its phosphorylation. Indeed, SHC1 knockdown markedly diminished the effect of MIG6 on ECs. Thus, our findings show that MIG6 is a potent endogenous inhibitor of angiogenesis that may have therapeutic value in anti-angiogenic therapy.